IPTEKS PENGAJUAN KREDIT BERDASARKAN INFORMASI AKUNTANSI PEMBERIAN KREDIT PADA PT BANK MANDIRI (PERSERO) TBK. AREA MANADO - Sumarauw, Ranggy D.F; Gerungai, Natalia Y. T. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Indonesian Banking in carrying out its business in economic democracy by using the principle of prudence, the main function of the bank is to collect funds and channel them back to the community. The role of banks in supporting economic activities is quite large because banks provide services in the circulation of money. Whereas from a banks point of view, credit has a strategic position which is one of the necessary sources of money in financing business activities that can be emphasized as the key to life for every human being. Agreement is a legal relationship in the field of wealth based on an agreement between legal subjects one with the other and between them bind to each other so that the law is obliged to implement the agreement agreed upon by the parties and cause legal consequences. By using a qualitative descriptive method from the results of the observation the author describes how the credit application process is carried out and how the crediting procedure is associated with accounting information in the provision of credit in this case to increase crediting at PT Bank Mandiri (persero) Tbk Manado Area. Based on observations the authors suggest that the independent bank must be more careful in making credit terminations so that there will be no bad credit.Keywords: credit applicaton, credit approval